Legal incorporation of mandatory marriage counseling prior to divorce in Peru - Eyzaguirre Rivas de Larios, Rocío del Pilar (2018)
This document aims to determine the suitability and importance of incorporate legally Mandatory Marriage Counseling as a prerequisite to the process of divorce in Peru. For this reason it is necessary to define the situation of divorce in the country, on the basis of statistical reports published by official entities and the legislative trend during recent decades regarding the legal figures relating to the separation and dissolution of the marriage; We will also indicate the result that a breakup generate in the life of the spouses, their children and the state and society as a whole. Finally, we’ll look at the figure of the previous mandatory marriage counseling, as a mechanism of support for couples in crisis; detailing its positive effects and exposing the criteria that guarantee its incorporation into our legal system.